Toward autonomous medicine: A comprehensive review of biomedical energy harvesting and wearable sensing systems - Riyamol Kallikkoden Razack (22254463) (2025)
The transition to a decentralized, continuous, and patient-centric healthcare model necessitates the development of energy-autonomous medical systems that can operate independently of traditional power sources. This review offers a comprehensive analysis of self-powered healthcare technologies that integrate biomedical energy harvesting (BEH) with autonomous sensing systems (ASS) to facilitate uninterrupted physiological monitoring and therapeutic interventions. Our research encompasses a diverse range of energy harvesting strategies, encompassing triboelectric, piezoelectric, thermoelectric, biochemical, and electromagnetic principles, while emphasizing the human body's function as a versatile energy storage system. Recent advancements in polymeric materials, which provide crucial properties such as flexibility, stretchability, biocompatibility, and biodegradability, making them indispensable in the design of wearable and implantable devices. From piezoelectric polymers, such as PLLA, to triboelectric materials embedded in smart textiles, polymers serve as the structural and functional backbone of next-generation energy harvesters and sensors. Their tunable mechanical and electrical properties enable seamless integration with soft tissues, allowing for the fabrication of conformable, miniaturized, and eco-friendly systems. The review also investigates strategies involving nano-structuring, microfabrication, and three-dimensional/four-dimensional printing to create miniaturized, conformable device architectures, alongside artificial intelligence (AI)/machine learning (ML)-driven simulations that enhance material selection and overall system performance. Through in-depth system-level integration, case studies, and an analysis of regulatory and translational challenges, this work presents a visionary perspective on implementing sustainable, intelligent, and fully autonomous self-powered healthcare platforms in real-world medical settings. Other Information Published in: Nano Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.nanoen.2025.111422